Rheumatological Manifestations of Diabetes Mellitus ─ An Update - Neki, NS; Singh, Riponjot; Aloona, Satpal; Singh, Bhupinder; Walia, Sargun Singh; Dhanju, Amandeep Singh (Journal of Enam Medical College, 2018)
Diabetes mellitus (DM) is a chronic metabolic condition and a major public health problem. It is associated with many musculoskeletal manifestations which are usually under-recognized and poorly treated, as compared to other complications like neuropathy, nephropathy and retinopathy. These manifestations affect the joints, soft tissues and the bones leading to alterations in musculoskeletal system of the patient. This article reviews the major rheumatological problems of diabetes mellitus including their management. J Enam Med Col 2018; 8(2): 94-100